Historiographical Analysis of Paul Zhytetsky’s (1837-1911) Educational and Enlightening Activity - Viktoriya Isachenko (Pedagogical Discourse, 2013)
The problem of Paul Zhytetsky’s educational and enlightening activity is analized  historiographically. P.Zhytetsky’s scientific creativity in the 20 th century is studied. The basic interpretation of works authored by the teacher in the context of social movements of the late nineteenth – early twentieth century is carried. The basic approaches to the interpretation of Zhytetsky’s historical research in the context of political life in Ukraine are presented. The basic periods of active social and scientific activities in the light of the views of P. Zhytetsky individual researchers are covered. The features of nonfiction materials authored by the teacher are characterised. Domestic and foreign scholars’ documentary and journalistic materials of the20–30-s of the twentieth century are viewed.